Effect of PV technology, solar tracker and electrolyzer type on electricity and hydrogen production in provincial centers of Pakistan: Finding the optimal angle and azimuth considering losses - Abdollahiarpanahi, Sajedeh; Jahangiri, Mehdi; Banitalebidehkordi, Alireza; Habib Ur Rahman Habib (Journal of power technologies, 2024)
Today, solar hydrogen has been proposed as a viable alternative to current fossil fuels in Pakistan. Therefore, in this work, for the first time, solar hydrogen production has been investigated in 6 centers of Pakistan province. PVGIS 5.2 software was used for simulation and different solar cell technologies were investigated. Considering the solar tracker in 3 modes: horizontal single-axis, vertical single-axis and two-axis, and considering the losses makes the results more comprehensive. The use of 4 different types of electrolyzers to produce hydrogen is another innovation of the present work. By performing sensitivity analysis, the optimal mounting angle and the optimal azimuth angle for the investigated station were found. The results showed that the optimal angle is between 28o to 32o and the optimal azimuth is between -17o to 4o for the investigated stations. For Gilgit and Peshawar stations, CIS technology is the most suitable, and CdTe technology is the most suitable for Quetta, Islamabad, Lahore and Karachi stations. Also, the vertical axis tracker is superior to the horizontal axis only in the Gilgit station, and the horizontal axis tracker is more suitable in the rest of the stations. Out of the 4 investigated electrolyzers, the SOE electrolyzer produces more hydrogen.